PENERAPAN SERVICE REQUEST MANAGEMENT PADA TATA KELOLA LAYANAN TEKNOLOGI INFORMASI - Ahmad Fitriansyah; Pahman Hasibuan (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
The purpose of this research is to design and implement a Service Request Management application and to improve the Service Request Management process at PT. Informatics Integration Partner based on Information Technology Service Management. This research is based on the need to manage the organization's information technology infrastructure and arrange the best services for users of information technology services that can provide a good quality foundation and quality assurance by using systematic process approaches and standard procedures for information technology services. This research is qualitative with data collection consisting of secondary data and primary data. Primary data is obtained from observations in the IT department and interviews with the head of the IT division on the Service Request work process and the existing database in the current Service Request Management application which has been processed using the help of Excel and Visio applications. While secondary data can be obtained through the website of PT. Informatics Integration Partners, as well as other additional data and information obtained from books, articles, and other scientific literature related to this research. The results of the research in the form of the proposed Service Request Management application system have several advantages and differences from the current system. Some of the advantages include: (1) Email notification when there is a request and change of request handling status; (2) Company data is safer and more secure because it is stored in a privacy server; (3) By using this system, the handling of a request can be monitored by the company's Top Level Management; (4) This system is easier to use because apart from being accessible through the website, it can also be accessed via mobile android